Peptidyl‐prolyl cis‐trans isomerase NIMA‐interacting 1 directly binds and stabilizes Nrf2 in breast cancer. Issue 1 (17th December 2021) - Saeidi, Soma; Kim, Su‐Jung; Guillen‐Quispe, Yanymee N.; Jagadeesh, Achanta Sri Venkata; Han, Hyeong‐jun; Kim, Seung Hyeon; Zhong, Xiancai; Piao, Juan‐Yu; Kim, Seong‐Jin; Jeong, Joon; Shin, Yun Jin; Cha, Yoon Jin; et al.
Abstract: Peptidyl‐prolyl cis ‐ trans isomerase NIMA‐interacting 1 (Pin1) has been frequently overexpressed in many types of malignancy, suggesting its oncogenic function. It recognizes phosphorylated serine or threonine (pSer/Thr) of a target protein and isomerizes the adjacent proline (Pro) residue, thereby altering folding, subcellular localization, stability, and function of target proteins. The oncogenic transcription factor, Nrf2 harbors the pSer/Thr‐Pro motif. This prompted us to investigate whether Pin1 could bind to Nrf2 and influence its stability and function in the context of implications for breast cancer development and progression. The correlation between Pin1 and Nrf2 in the triple‐negative breast cancer cells was validated by RNASeq analysis as well as immunofluorescence staining. Interaction between Pin1 and Nrf2 was assessed by co‐immunoprecipitation and an in situ proximity ligation assay. We found that mRNA and protein levels of Pin1 were highly increased in the tumor tissues of triple‐negative breast cancer patients and the human breast cancer cell line. Genetic or pharmacologic inhibition of Pin1 enhanced the ubiquitination and degradation of Nrf2. In contrast, the overexpression of Pin1 resulted in the accumulation of Nrf2 in the nucleus, without affecting its transcription. Notably, the phosphorylation of Nrf2 at serine 215, 408, and 577 is essential for its interaction with Pin1. We also identified phosphorylated Ser104 and Thr277 residues in Keap1, a negative regulator of Nrf2, for Pin1 binding. Pin1 plays a role in breast cancer progression through stabilization and constitutive activation of Nrf2 by competing with Keap1 for Nrf2 binding.